A short-lived republic: December 5-6, 1918. - Szávai, Ferenc (Acta Scientiarum Socialium, 2018)
A less known chapter of Hungarian historiography features the state-forming attempts taking place within the territory of the dualist state during 1918‒1919. These failed as they were unable to gain international recognition, were poorly prepared, or their independence efforts did not prevail among opposing interests. One of these attempts was the Heinzenland/Hoanznlaund Republic, existing for two days. This paper presents the very short history of the Republic of Heinzenland.
Keywords: Great War (1914‒1918); history of Central-Europe; History of Hungary; birth of the first Austrian Republic; history of Republic of Heinzenland; Vienna